My chinese village (east Turkistan) - Nagy, Luqman (Goodword Books New Delhi, 2004)
"My Chinese Village (East Turkistan)" by Luqman Nagy offers a detailed glimpse into the traditions, culture, and everyday life of a village in East Turkistan, China.